Association of PSCA rs2294008 gene variants with poor prognosis and increased susceptibility to gastric cancer and decreased risk of duodenal ulcer disease. Issue 6 (19th March 2015) - García‐González, María Asunción; Bujanda, Luis; Quintero, Enrique; Santolaria, Santos; Benito, Rafael; Strunk, Mark; Sopeña, Federico; Thomson, Concha; Pérez‐Aisa, Angeles; Nicolás‐Pérez, David; Hijona, Elizabeth; Carrera‐Lasfuentes, Patricia; et al.
<x xml:space="preserve">Abstract</x> Two recent genome‐wide association studies in Asians have reported the association between the PSCA (prostate stem cell antigen) rs2294008C>T gene polymorphism and two Helicobacter pylori infection‐related diseases such as gastric cancer (GC) and duodenal ulcer (DU). Since rs2294008 allele frequencies differ notably among ethnicities, we aimed to assess the role of rs2294008 on the susceptibility to GC and DU in a Caucasian population in Spain. Moreover, the relevance of rs2294008 on GC prognosis was evaluated. Genomic DNA from 603 Spanish patients with primary GC, 139 with DU and 675 healthy controls was typed for the PSCA rs2294008C>T polymorphism by PCR‐TaqMan assays. H. pylori infection [odds ratio (OR): 8.27; 95% confidence interval (CI): 3.45–15.33] and nonsteroidal anti‐inflammatory drugs (OR: 6.54; 95% CI: 3.19–12.43) were identified as independent risk factors for DU whereas the rs2294008T allele was associated with reduced risk of developing the disease (OR: 0.52; 95% CI: 0.33–0.82). Infection with CagA strains (OR: 2.10; 95% CI: 1.63–2.34), smoking (OR: 1.93; 95% CI: 1.54–2.61), family history of GC (OR: 2.83; 95% CI: 2.01–3.83), and the rs2294008T allele (OR: 1.46; 95% CI: 1.07–1.99) were associated with increased risk of GC. Interestingly, the association with the rs2294008T allele was restricted to noncardia GC (OR: 1.43; 95% CI: 1.12–1.82), particularly of the diffuse histotype (OR: 1.59; 95% CI: 1.16–1.92). Finally, Cox regression analysis identified the rs2294008T variant as a prognosis factor associated with worse overall survival in patients with diffuse‐type GC (hazard ratio: 1.85; 95% CI: 1.12–3.06). From these results we conclude that the PSCA rs2294008 polymorphism is involved in the susceptibility to GC and DU, as well as in the prognosis of the diffuse‐type of GC in Caucasians.